Group including a woman in front of Clondyke Trading Company, Skagway, probably between 1897 and 1899 - Warner, Arthur Churchill, 1864-1943 (1897)
Small sign in front reads: Located by F.H. Reid After gold was discovered in the Yukon Territory, thousands of people left for the Klondike to join in the gold rush in the Summer of 1897. Frank Reid was a bartender at the Klondike Saloon and later was appointed town surveyor on August 18, 1897 and helped map the town of Skagway. Killed in a shootout with the outlaw Jefferson "Soapy" Smith. Warner 101 Filed in Alaska series.